THE EFFECT OF OPERATING CAPACITY, LIQUIDITY, AND PROFITABILITY ON FINANCIAL DISTRESS IN FOOD AND BEVERAGE SUB-SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE PERIOD 2016-2020 - Sudaryono; Bagus Nurcahyo; Ika Puji Saputri (International Journal Management and Economic, 2023)
The purpose of this research is to identify and analyze the effect of operating capacity, liquidity, and profitability on financial distress in food and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the 2016-2020 period. To implement these objectives, the panel data regression analysis method is used. and using the Altman method as a classification of companies experiencing financial distress. The type of data used is secondary data obtained from official websites and websites owned by each food and beverage company. The population of this study were 27 food and beverage sub-sector companies listed on the Indonesia Stock Exchange in 2022. Sampling used a purposive sampling method with several specific criteria. There are 12 companies that meet the criteria to be sampled in this study. The results of research with the help of Eviews 9 show that operating capacity as measured by total asset turnover (TATO) partially has no effect on financial distress while liquidity is measured by current ratio (CR) and profitability as measured by return on assets (ROA) partially effect on financial distress. Then simultaneously operating capacity, liquidity, and profitability affect financial distress.